Screening of Rice Mutants for Salinity Tolerance and Yield - Sakina khanam; Md. Mahmud Al Noor; Md. Sabibul Haque (Fundamental and Applied Agriculture, 2023)
Soil salinity decreases rice yield by 20%, affecting global rice production including in Bangladesh. Some advanced mutant lines were developed through mutation breeding to observe the performance against salinity at the seedling stage. Mutant lines that are tolerant to salinity at the seedling stage can be used to develop salt tolerant varieties. The first experiment evaluated the salinity tolerance of 20 rice genotypes grown under hydroponic conditions at the seedling stage using a completely randomized design (CRD). Binadhan-10 was used as a salt-tolerant check variety.Salinity level of 15 dS/m, shoot length (SL) and shoot weight (SW) were reduced by 5-44% and 12-22%, respectively, in tolerant genotypes and by 51-73% and 26-75% in susceptible genotypes compared to the control condition. Root length (RL) had a marginal reduction of 10-27% in tolerant genotypes and 18-38% in susceptible genotypes. Susceptible genotypes showed drastic change in SL, SW, shoot dry weight (SDW) and root dry weight (RDW) compared to the tolerant genotypes. According to the heatmap, growth parameters SL, SW, SDW, and RDW formed cluster I while RL formed cluster II. According to the radar plot clustering, tolerant genotypes were in cluster-I, moderately tolerant genotypes in cluster-II, and susceptible genotypes in cluster-III, respectively. Four lines (L-4-P-1-1, LIRG-4Seg 1(1)-3, L-4-P-1(1), and L-4- P-1-P-2) identified as salt tolerant. The second experiment evaluated the yield performance of these lines under normal field conditions. The mutant line LIRG-4Seg-1(1)-3 exhibited higher yield (7.6 t/ha) with higher number of effective tillers per plant (9.0) compared to the tested mutants and a longer panicle length (28.9 cm) compared to Binadhan-10 (23.5 cm). This line along with other selected mutants can be further screened at the reproductive phase or utilized as breeding material to develop a salt tolerant variety. [Fundam Appl Agric 2023; 8(4.000): 730-738]